Sharing cities: creating space and practice for new urban agency, capacities and subjectivities. Issue 4 (8th August 2019) - Santala, Inka; McGuirk, Pauline
ABSTRACT: In recent years, cities across the world have witnessed the emergence of alternative economic practices that have come to challenge norms related to production and consumption. Although a plethora of research has started to emerge on this sharing economy, less attention has been paid to community-led and potentially transformative sharing practices that prioritize peer-to-peer collaboration, equity, and increasing social capital above financial benefits. Following the work of a community-based initiative Share Sydney, this research seeks to understand practices of communal sharing as they emerge in the City of Sydney, Australia. Drawing analysis particularly from the group's Sharing Map project, we explore how communal sharing initiatives like Share Sydney are constituting sharing practice and seeking to develop new kinds of urban agency, capacities, and subjectivities that may feed progressive community development towards more socially just and environmentally sustainable Sharing Cities.